Nonislet Cell Tumor Hypoglycemia. (1st October 2013) - Thomas, Johnson; Kumar, Salini C.
Abstract : Nonislet cell tumor hypoglycemia (NICTH) is a rare cause of hypoglycemia. It is characterized by increased glucose utilization by tissues mediated by a tumor resulting in hypoglycemia. NICTH is usually seen in large mesenchymal tumors including tumors involving the GI tract. Here we will discuss a case, its pathophysiology, and recent advances in the management of NICTH. Our patient was diagnosed with poorly differentiated squamous cell carcinoma of esophagus. He continued to be hypoglycemic even after starting continuous tube feeds and D5W. General workup for hypoglycemia was negative and insulin-like growth factor II (IGF II) was in the normal range. Hypoglycemia secondary to "big" IGF II was considered, and patient was started on steroids. His hypoglycemia resolved within a day of treatment with steroids. Initially patient had hypoglycemia unawareness, which he regained after maintaining euglycemia for 48 hours.